Enquêter avec et auprès des jeunes en difficulté en contexte africain : une démarche méthodologique par le bas - Moriké Dembele; Ibrahima Traoré (Sociétés et Jeunesses en Difficulté)
This article reflectively reports on a research experience carried out in the frame of a PhD thesis in educational science related to the social future of street children, placed or not in a social safeguarding institution, in two West-African cities: Dakar and Bamako. The surveyed youths, as participants’ in a Master’s project (Dembélé, 2005), who were contacted through an intermediary, became interviewers at the PhD project phase. In fact, the young interviewers are invited to give an account of their own lives, before asking the other children and young people they surveyed to tell the stories of their lives too. Then, the interviewers are asked to transcribe the stories of their life and put these stories in a chronological order for later checking by the authors of the stories so that they can eventually amend their stories at the end of the review of their past life. Using these methodological choices, the life stories of two hundred former street children, who have become young-adults, were collected by twenty five young people. This research experience results in a theoretical, methodological, and epistemological analysis at the same time. This research model questions on the following: What meaning can be given to the words collected from a child or a young man by other children and young people having similar life paths? What are the advantages and limitations of this surveying approach by immersion through an intermediary involving children and young people? What precautions are to be taken to overcome the obstacles to empirical data collection by the youths who are themselves concerned by a similar study?